2011
DOI: 10.1183/09031936.00044310
|View full text |Cite
|
Sign up to set email alerts
|

Nasal nitric oxide and nitric oxide synthase expression in primary ciliary dyskinesia

Abstract: No study has evaluated the correlation between different expression of nitric oxide synthase (NOS) isoforms in nasal epithelial cells and nasal NO (nNO) level in primary ciliary dyskinesia (PCD).Gene expression of endothelial (NOS3) and inducible NOS (NOS2) and their correlation with nNO level, ciliary function and morphology were studied in patients with PCD or secondary ciliary dyskinesia (SCD). NOS3 gene polymorphisms were studied in blood leukocytes.A total of 212 subjects were studied (48 with PCD, 161 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 30 publications
3
35
0
Order By: Relevance
“…Recent reports reinforce the suggestion that low levels of nNO can be used as a screening tool for the early identification of PCD patients [20,26] and that they are indicative of disease also in uncooperative children when they remain persistently low and when other diseases have been excluded [27]. Our present data confirms that nNO levels in PCD patients are very low, which is in agreement with previous studies [2,4,7].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Recent reports reinforce the suggestion that low levels of nNO can be used as a screening tool for the early identification of PCD patients [20,26] and that they are indicative of disease also in uncooperative children when they remain persistently low and when other diseases have been excluded [27]. Our present data confirms that nNO levels in PCD patients are very low, which is in agreement with previous studies [2,4,7].…”
Section: Discussionsupporting
confidence: 83%
“…In a recent study of ours we confirmed that NO gas is implicated in the modulation of ciliary function in PCD patients [26]. This study could reflect the correlation between NO and ciliary function, which may explain some of the nNO levels and clinical variability of the disease.…”
Section: Discussionsupporting
confidence: 65%
“…Four studies reported nNO levels in consecutive referrals to a PCD diagnostic service; two were excluded (lack of sampling details and unclear PCD diagnosis) [19,33]. CORBELLI et al [10] Seven studies compared nNO levels in PCD patients with those in non-CF bronchiectasis (table 4).…”
Section: Study Selection and Risk Of Biasmentioning
confidence: 99%
“…In healthy individuals, nNO is produced by the paranasal sinuses via the action of the enzyme nitric oxide synthase (NOS). 13 In the respiratory epithelium, the action of…”
Section: Introductionmentioning
confidence: 99%